2021
DOI: 10.21053/ceo.2020.00199
|View full text |Cite
|
Sign up to set email alerts
|

Usage and Diagnostic Yield of Fine-Needle Aspiration Cytology and Core Needle Biopsy in Thyroid Nodules: A Systematic Review and Meta-Analysis of Literature Published by Korean Authors

Abstract: Objectives. The usefulness of core needle biopsy (CNB) for the diagnosis of thyroid nodules remains controversial, and preferences vary across hospitals. The purpose of this study was to assess the actual use of CNB in Korea and to analyze the advantages and disadvantages of CNB through a systematic review and meta-analysis of papers published by Korean authors. Methods. A meta-analysis of full-text publications published in English presenting data from Korea retrieved from the Embase literature database was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…In recent years, core needle biopsy (CNB) from thyroid nodules has been recommended for previous inconclusive FNAs [ 21 ]. Also, some researchers have confirmed that CNB could overcome the limitations of FNA in these lesions [ 10 , 13 , 22 , 23 ]. However, the role of CNB has not been well established for the assessment of thyroid nodules with suspicious US features [ 10 ].…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, core needle biopsy (CNB) from thyroid nodules has been recommended for previous inconclusive FNAs [ 21 ]. Also, some researchers have confirmed that CNB could overcome the limitations of FNA in these lesions [ 10 , 13 , 22 , 23 ]. However, the role of CNB has not been well established for the assessment of thyroid nodules with suspicious US features [ 10 ].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, CNB has been increasingly utilized as a first-line diagnostic tool for initially detected thyroid nodules [11]. However, recent meta-analysis reported that CNB had higher proportion of indeterminate follicular lesions than FNA, with 72% of nodules diagnosed as indeterminate follicular lesions on CNB being due to architectural atypia [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the diagnosis and prevention of OSCC, emphasis is placed on identifying potential malignant lesions of the oral mucosa and local diseases that promote chronic inflammation, mainly relying on objective clinical examinations and surgical biopsy 5 , 6 . Although surgical biopsy is the gold standard for the diagnosis of OSCC, it is somewhat invasive and can sometimes be harmful to patients 7 .…”
Section: Introductionmentioning
confidence: 99%